Kisah Al-Qur’an sebagai Media Pendidikan - Zenal Satiawan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The purpose of this study is to determine the urgency of the stories of the Qur’an and how the contents of the educational value in it. The research method in this journal uses the method of library research, then analyzed using the content analysis method, which is descriptive-analytic with the main source of the Qur'anic stories. The secondary sources consist of articles, journals, and other books related to the research topic. Education through stories is very important, because naturally it is liked by everyone at various ages. Verses and guidance in the stories of the Qur'an are also more numerous than verses that talk about the law. In the Qur'an there is a story about the people of the past, the story of the time of the Prophet and the stories of the future, and they all become one of the methods for conveying messages of faith and strengthening efforts to deliver them to mankind that lead to the values of monotheism, worship and morals and the values of da'wah. Regarding the repetition of the story of the Qur'an, the aim is to give great attention to the story so that messages are more stable and embedded in the soul. This is because repetition is one of the ways of confirmation and an indicator of how much attention is paid. Stories that contain role models can be used as lessons to be followed by goodness, while stories that cannot be exemplary can be used as lessons as a means of increasing awareness.